Dresing Collection. - Petersen, Vibeke (London : The Merla Art Foundation, 2008)
Alfelt, Else ; Arman ; Armitage, Kenneth ; Arp, Hans (Jean) ; Atlan, Jean-Michel ; Bille, Ejler ; Bindesboll, Thorvald ; van Velde, Bram ; Buffet, Bernard ; Calder, Alexander ; César ; Chadwick, Lynn ; Corneille ; Delaunay, Sonia ; Deyrolle, Jean ; Draper, Markus ; Dubuffet, Jean ; Dufy, Raoul ; Eckersberg, Christoffer Wilhelm ; Ernst, Max ; Estes, Richard ; Estève, Maurice ; Fontana, Lucio ; Francis, Sam ; Gilbert & George ; Golder, Andreas ; Hatoum, Mona ; Haugen Sorensen, Jorgen ; Heerup, Henry ; Hirst, Damien ; Hockney, David ; Host, Oluf ; Isakson, Karl ; Jacobsen, Egill ; Jacobsen, Robert ; Jorn, Asger ; Kandinsky, Wassily ; Kiefer, Anselm ; Kirkeby, Per ; Lanskoy, André ; Lapicque, Charles ; Lundstrom, Vilhelm ; Meese, Jonathan ; Miller, Henry ; Mitchell, Joan ; Mortensen, Richard ; Pedersen, Carl-Henning ; Picabia, Francis ; Picasso, Pablo ; Poliakoff, Serge ; Polke, Sigmar ; Pollock, Jackson ; Pomodoro, Arnaldo ; Quinn, Marc ; Rauch, Neo ; Richter, Gerhard ; Rodin, Auguste ; Rodriguez, René Francisco ; Rosenquist, James ; de Saint Phalle, Niki ; Soulages, Pierre ; Stella, Frank ; Tal R ; Tobiasse, Théo ; Warhol, Andy ; Weie, Edvard ; Willumsen, Jens Ferdinand ; Woods, Clare
boek